Using smart strategy to improve the tenth graders’ reading comprehension achievement in an ESP class - Wijayanti, Anna Estu (Linguista: Jurnal Ilmiah Bahasa, Sastra, dan Pembelajarannya, 2023)
This study aims to find out how well SMART Strategy improves the tenth graders' reading comprehension achievement in ESP at Cendekia Vocational High School Madiun. The subjects of this study consisted of 30 students of tenth graders majoring in Multimedia. In conducting this research, researchers used Classroom Action Research. The researcher used the SMART (Self-Monitoring Approach Reading and Thinking) strategy in teaching ESP texts. This research was conducted by following the steps of action research: planning, action, observation, and reflection. This research was conducted in three cycles. Each cycle consists of two meetings. Data obtained through tests, observation sheets, field notes and documentation. The results of this study indicate that there is an increase in students' ability to understand reading ESP texts by using the SMART strategy. Most students get good grades in the second cycle. The minimum passing criteria for English subject is 75. The students' average score on the pre-test was 57.17. The average score of students in post-test I was 67, the average score of students in post-test II was 78.67. Then the average value of post-test 3 increased 87.33 this shows that in cycle I there were 40% of students who achieved KKM and increased in cycle II to 77% of students who achieved KKM and in cycle III reached 100%. Its means the research has reached the criteria of success 100% where 30 students passed the reading comprehension test. Therefore, it can be concluded that the SMART strategy was able to improve the reading comprehension